Value-for-money e geração de valor público na atuação das organizações sociais de saúde: contribuições para o governo do estado de São Paulo - Souza, Lívia Magro de (2015)
The fact that the Brazilian State shall, in accordance with its Constitution, guarantee the right of its citizens to health does not necessarily mean that the provision of these services must be made directly by the government. Partnerships with social organizations, established by Federal Law 9.637 / 1998 and regulated by the Management Contract, claim to offer an alternative to the efficiency, agility and flexibility in health care. However, the structure of management contracts with Health Social Organizations (OSS, in Portuguese), drawn up with the negotiation of goals and performance indicators, cannot be considered, in isolation, as guarantee factor to the adequate provision of such public services. In this context, it is crucial to consider the arrangements organized by the government to ensure that the services offered represent what citizens consider value. This work focuses on the partnerships established with OSS under the state government of Sao Paulo. The interviews and research undertaken for this study show that, in order to operate this partnerships from the perspective of value-for-money and fostering public value, it is necessary to implement some improvements, such as: the listening mechanisms to citizens, collaborative governance arrangements among federated entities, alignment with regulatory agencies and, above all, qualifying the organizational capacity of the state and OSS, through the review of the willing targets and indicators in management contracts.